The Evaluation of Several Alternative Policies’ Impact on The Mandarin (Citrus Reticulata) Industry in Indonesia: A System Dynamics Analysis - lyli mufidah; Fatimah Mohamed Arshad; Shaufique Sidique; Agus Sugiyatno; Abdulla Ibragimov (Agro Ekonomi, 2019)
The increase in imports and the decline in Indonesia's production triggered the government’s intervention in the form of non-tariff barriers. This will surely make a change in Indonesia's mandarin landscape industry. Therefore, this paper aims to construct structured factors building the mandarin industry and attempts to evaluate the impact of several alternative policies, including the non-tariff barriers imposed, in the purpose to find the policies that sustain the industry in the future. Systems dynamics are employed due to their ability to accommodate time delay and reciprocal relationships between sub-systems found in the industry. The time series data of mandarin from BPS were used in this research from 1999 to 2012, which includes production, productive area, productivity, price, local consumption and import.The first step is to construct the existing pattern of the mandarin industry in Indonesia. Afterward, six different scenarios were simulated, including the non-tariff barriers; and they were compared for their ability to sustain the Indonesian mandarin industry. The ability was assessed from the relative value, production, expected profits and import value. The analysis results recommend the government to pay more attention to the disease management and to improve the ratio of agricultural extension agents to areas, which can lead to a more significant impact on the mandarin industry in Indonesia, even with the gradual elimination of non-tariff barriers.